War in international society - Pejcinovic, Lacy. (New international relations., 2013)
"Is war an institution of international society and how is it constituted as such across the evolution of international society? This book is an inquiry into the purpose of war as a social institution, as originally put forward by Hedley Bull. It offers a comprehensive examination of what is entailed in thinking of war as a social institution and as a mechanism for order"--